Neural responses to negative outcomes predict success in community‐based substance use treatment. (3rd February 2017) - Forster, Sarah E.; Finn, Peter R.; Brown, Joshua W.
Abstract: Background and aims: Patterns of brain activation have demonstrated promise as prognostic indicators in substance dependent individuals (SDIs) but have not yet been explored in SDIs typical of community‐based treatment settings. Design: Prospective clinical outcome design, evaluating baseline functional magnetic resonance imaging data from the Balloon Analogue Risk Task (BART) as a predictor of 3‐month substance use treatment outcomes. Setting: Community‐based substance use programs in Bloomington, Indiana, USA. Participants: Twenty‐three SDIs (17 male, aged 18–43 years) in an intensive outpatient or residential treatment program; abstinent 1–4 weeks at baseline. Measurements: Event‐related brain response, BART performance and self‐report scores at treatment onset, substance use outcome measure (based on days of use). Findings: Using voxel‐level predictive modeling and leave‐one‐out cross‐validation, an elevated response to unexpected negative feedback in bilateral amygdala and anterior hippocampus (Amyg/aHipp) at baseline successfully predicted greater substance use during the 3‐month study interval ( P  ≤ 0.006, cluster‐corrected). This effect was robust to inclusion of significant non‐brain‐based covariates. A larger response to negative feedback in bilateral Amyg/aHipp was also associated with faster reward‐seeking responses after negative feedback ( r (23)  = −0.544, P  = 0.007; r (23)  = −0.588, P  = 0.003). A model including Amyg/aHipp activation, faster reward‐seeking after negative feedback and significant self‐report scores accounted for 45% of the variance in substance use outcomes in our sample. Conclusions: An elevated response to unexpected negative feedback in bilateral amygdala and anterior hippocampus (Amyg/aHipp) appears to predict relapse to substance use in people attending community‐based treatment.